Macrosomia in non-gestational diabetes pregnancy:glucose tolerance test characteristics and feto-maternal complications in tropical Asia Pacific Australia - Aranha, Algenes; Malabu, Usman H; Vangaveti, Venkat; Reda, Elham Saleh; Tan, Yong Mong; Sangla, Kunwarjit Singh (Asian Pacific journal of tropical biomedicine, 2014)
Objective:To look into the glucose tolerance test characteristics and determine complications in non-gestational diabetes pregnant subjects.Methods:From 2006 to 2009 all non-gestational diabetes mellitus(non-CDM)pregnant women who delivered macrosomia at the North Australia’s Townsville Hospital were retrospectively reviewed by extracting data from clinical record.Glucose tolerance tests results were analysed in the light of an earlier diagnosis of non-GDM.Results:Ninety-one non-CDM mothers with macrosomia were studied and compared with 41normoglycemic subjects without macrosomia.Of the subjects with non-GDM macrosomia,45(49.4%)had normal SO g glucose challenge test(GCT)without further testing,another 8(8.8%)had abnormal GCT but normal 75 g oral glucose tolerance test(OGTT).A total of 4(4.4%)subjects had normal GCT and OGTT.Interestingly.14 out of 16(87.5%)subjects who were tested with OGTT owing to past history of macrosomia had normal results but delivered macrosomic babies.Only 12 subjects had both GCT and OGTT,the rest of the cohort had either of the two tests.Subjects with non-CDM macrosomia had higher frequency of neonatal hypoglycaemia 34%as compared to 10%in nonmacrosomic babies(P=0.003).Other feto-maternal complications were similar in both groups.Conclussions:No significant pattern of glucose tolerance characteristics was identified in nonGDM mothers with macrosomic babies.In spite of being normoglycemic significant neonatal hypoglycaemia was recorded in non-GDM macrosomic babies.Further prospective studies on a larger population are needed to verify our findings.